Narušenija pokazatelej «srocnoj» adaptacii v processe naprjažennoj trenirovocnoj raboty vysokokvalificirovannych sportsmenov i sredstva ich profilaktiki - Iordanskaja, F. A. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
The studies are based on the results of dynamic medical and biological observations of elite athletes in the course of training activities, at the preparatory and pre-competition stages of preparation. The frequency of subjective indicators of load tolerance and the frequency of objective indicators of disruption of the processes of "urgent" adaptation of physiological systems and functions ensuring athletic performance, and biochemical adaptation indicators. It is established that during the preparatory stage in conditions of shock training loads athletes complain of impaired well-being and tolerance of training loads and in 9% of those surveyed an unsatisfactory functional condition with symptoms of disadaptation to exercise is diagnosed. At the pre-competition stage, subjective signs of impaired well-being and load tolerance are usually not presented against the background of improving the level of functional preparedness. Athletes at the same time have transient symptoms of violation of "urgent" adaptation and delayed under-recovery, in 30% of cases requiring recovery activities.